Evaluation of BIPM vis-a-vis farmer practices on rice (Oryza sativa) insect-pests in relation to weather parameters in the Tarai region of Uttarakhand - RIYA,; MAURYA, R P (The Indian Journal of Agricultural Sciences, 2026)
The experiment was conducted during the rainy (kharif) season of 2021 (June to October, 2021) at the Norman E. Borlaug Crop Research Centre, Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to compare Bio-Intensive Pest Management (BIPM) practices with farmer’s practices (FP) in rice. BIPM included green manuring, transplanted border crops, seed treatment, pheromone traps, augmentative releases of Trichogramma japonicum, and spraying of 1% neem oil, whereas FP mainly depends on chemical insecticides. BIPM plots recorded lower incidences of yellow stem borer (YSB), brown plant hopper (BPH), and leaf folder, along with higher populations of natural enemies. Although BIPM plots showed slightly higher dead hearts, they had fewer white ear heads, higher grain yield, and a better cost-benefit ratio compared to FPP. Correlation studies revealed a significant positive relationship between YSB incidence and maximum temperature. While BPH was positively correlated with minimum temperature and relative humidity in BIPM plots, predator species such as dragonflies and damselflies also showed a positive correlation with minimum temperature in BIPM plots. The above information showed that BIPM packages and frequently pest monitoring have significantly reduced insect-pests and increased natural enemies in BIPM fields compared to FPP. Green manuring increases crop nutrients availability, reducing the need for additional nitrogen treatment. Seed treatment with PBA-3 eliminated bacterial and fungus diseases in BIPM plots. BIPM offers a superior benefit-cost ratio, boosting crop production and maintaining ecological balance. It is economically more affordable, suppresses major insect-pests and supports sustainable farming practices.